Relationship between non- performing loans, industry, and economic growth of the african economies and policy recommendations for global growth - Dinçer, Hasan; Yüksel, Serhat; Adalı, Zafer (IGI Global, 2018)
The main purpose of this chapter is to evaluate the causality relationship between non-performing loans, industry volume, and economic growth and to provide some policy recommendations for global growth. Within this context, annual data of 16 African countries for the periods between 2001 and 2015 was taken into the consideration. Additionally, Dumitrescu Hurlin panel causality test was used to reach the objective. According to the result of this analysis, it was identified that there is a causality relationship between industry volume and economic growth. In addition to this situation, it was also defined that a decrease in economic growth is the main cause of the non-performing loans ratio in African countries. This chapter makes an important contribution to the literature. While considering these results, it can be said that to increase global trade economies of the countries should be improved and banking sectors should work more effectively. As a result, it will be possible to increase the living standards of the people and provide global growth.
Keywords: Non-Performing Loans; Banks; Loans NPLs